A conserved ankyrin repeat-containing protein regulates conoid stability, motility and cell invasion in Toxoplasma gondii. Issue 1 (December 2017) - Long, Shaojun; Anthony, Bryan; Drewry, Lisa; Sibley, L. David
Abstract Apicomplexan parasites are typified by an apical complex that contains a unique microtubule-organizing center (MTOC) that organizes the cytoskeleton. In apicomplexan parasites such asToxoplasma gondii, the apical complex includes a spiral cap of tubulin-rich fibers called the conoid. Although described ultrastructurally, the composition and functions of the conoid are largely unknown. Here, we localize 11 previously undescribed apical proteins inT .gondii and identify an essential component named conoid protein hub 1 (CPH1), which is conserved in apicomplexan parasites. CPH1 contains ankyrin repeats that are required for structural integrity of the conoid, parasite motility, and host cell invasion. Proximity labeling and protein interaction network analysis reveal that CPH1 functions as a hub linking key motor and structural proteins that contain intrinsically disordered regions and coiled coil domains. Our findings highlight the importance of essential protein hubs in controlling biological networks of MTOCs in early-branching protozoan parasites. Apicomplexan parasites such asToxoplasma gondii possess a tubulin-rich structure called the conoid. Here, Long et al. identify a conoid protein that interacts with motor and structural proteins and is required for structural integrity of the conoid, parasite motility, and host cell invasion.